SlNAC1, a stress‐related transcription factor, is fine‐tuned on both the transcriptional and the post‐translational level - Huang, Weizao; Miao, Min; Kud, Joanna; Niu, Xiangli; Ouyang, Bo; Zhang, Junhong; Ye, Zhibiao; Kuhl, Joseph C; Liu, Yongsheng; Xiao, Fangming (The New phytologist, 2013)
The plant‐specific NAC (NAM, ATAF1,2, CUC2) transcription factors play significant roles in diverse physiological processes. In this study, we determined the regulation of a stress‐related tomato (Solanum lycopersicum) NAC1 (SlNAC1) transcription factor at both the transcriptional and the post‐translational level. The SlNAC1 protein was found to be stable in the presence of proteasome‐specific inhibitor MG132 or MG115 and ubiquitinated in plant cells, suggesting that the SlNAC1 is subject to the ubiquitin–proteasome system‐mediated degradation. Deletion analysis identified a short segment of 10 amino acids (aa261–270) that was required for ubiquitin–proteasome system‐mediated degradation, among which two leucine residues (L268 and L269) were critical for the protein instability of SlNAC1. Fusion of the degron (SlNAC1₁₉₁–₂₇₀) containing these 10 amino acids to green fluorescent protein was found to be sufficient to trigger the degradation of the fusion protein. In addition, the SlNAC1 gene is strongly upregulated during Pseudomonas infection, while repression of the NAC1 ortholog in Nicotiana benthamiana resulted in enhanced susceptibility to Pseudomonas bacteria. These results suggest that rapid upregulation of the NAC1 gene resulting in more protein production is likely one of the strategies plants use to defend themselves against pathogen infection.